Sexual Orientation and Gender Identity Discrimination - Lau, Holning (Brill Research Perspectives, 2018)
In Sexual Orientation and Gender Identity Discrimination Holning Lau offers an incisive review of the conceptual questions that arise as legal systems around the world grapple with whether and how to protect people against sexual orientation and gender identity discrimination. Readership: All interested in LGBT rights (i.e., SOGI rights). This audience ranges from students to seasoned LGBT rights experts who specialize in a particular country/region and are seeking to learn about other parts of the world.